2021
DOI: 10.1063/5.0032743
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann modeling and simulation of forced-convection boiling on a cylinder

Abstract: When boiling occurs in a liquid flow field, the phenomenon is known as forced-convection boiling. We numerically investigate such a boiling system on a cylinder in a flow at saturated conditions. To deal with the complicated liquid-vapor phase-change phenomenon, we develop a numerical scheme based on the pseudopotential lattice Boltzmann method (LBM). The collision stage is performed in the space of central moments (CMs) to enhance numerical stability for high Reynolds numbers. The adopted forcing scheme, cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 108 publications
0
17
0
Order By: Relevance
“…48,49 Therefore, it is time to extend CLBM to simulate the more challenging thermal multiphase flow, e.g., the boiling process. More recently, CLBM has been employed to simulate twodimensional (2D) forced-convection boiling on a cylinder by Saito et al, 50 while the present work further extends CLBM to a much larger thermal multiphase system, i.e., the three-dimensional (3D) pool boiling.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…48,49 Therefore, it is time to extend CLBM to simulate the more challenging thermal multiphase flow, e.g., the boiling process. More recently, CLBM has been employed to simulate twodimensional (2D) forced-convection boiling on a cylinder by Saito et al, 50 while the present work further extends CLBM to a much larger thermal multiphase system, i.e., the three-dimensional (3D) pool boiling.…”
Section: Introductionmentioning
confidence: 75%
“…The above settings approximately correspond to the saturated water-vapor system at temperature 556 K and pressure 7 MPa. 50 Following Refs. 30, 33, and 34, the specific heat at constant volume is set to be constant, cv = 6.0, in the whole computational domain.…”
Section: Numerical Simulations and Analysismentioning
confidence: 99%
“…The saturated coexistence densities can be correctly reproduced by the mechanical stability adjustment method developed by Li et al [56,57]. The hybrid formulation was subsequently extended to CLBM and systematically verified [53,58]. Moreover, it was shown that the resulting hybrid multiphase CLBM had superior stability and was able to simulate large-scale pool boiling [53] and forced-convection boiling [58] systems covering the complete boiling curve and typical boiling regimes.…”
Section: A Hybrid Pseudopotential Clbmmentioning
confidence: 91%
“…Moreover, it was shown that the resulting hybrid multiphase CLBM had superior stability and was able to simulate large-scale pool boiling [53] and forced-convection boiling [58] systems covering the complete boiling curve and typical boiling regimes. In this study, the treatments proposed by Saito et al [58] and Fei et al [53] are combined and adopted for both 2D and 3D simulations. Using the Chapman-Enskog analysis, the following macroscopic equations can be recovered:…”
Section: A Hybrid Pseudopotential Clbmmentioning
confidence: 99%
“…LBM received a growing interest motivated by its scalability and its low dissipation properties, making it particularly well-suited for acoustic long distance dispersion problems 20 . It has been applied to a wide range of applications such as, reservoir permeability [21][22][23] , combustion flows 24 , blood flow 25 , boiling flow 26 , thermocapillarity flows 27 , non-Newtonian flows 28 , magneto-hydrodynamic flows 29 , cryogenic flows 30 , etc.…”
Section: Introductionmentioning
confidence: 99%